COMMUNICATIVE COMPETENCE IMPROVEMENT OF SENIOR NURSES AS THE BASIS OF HEALTH PROMOTING ENVIRONMENT FORMATION AT A PEDIATRIC INPATIENT HOSPITAL - I. M. Spivak; E. G. Biryukova (Union of pediatricians of Russia, 2014)
This article is dedicated to dependence of psychological and somatic well-being of sick children on the quality of social environment at an inpatient hospital. The authors emphasize the crucial role of the nurse's personality in the formation of a favorable unit environment regarding the child's psychological condition. They cite data of a study of risk factors reducing quality of labor activity of the nursing staff. The authors describe psychological aspects of teaching professional communication skills to senior nurses in order to form health promoting environment at a pediatric inpatient hospital. They evaluate efficiency of communicative competence improvement of senior nurses.